Enhancing expressive natural playing experience for virtual kompang using tri-axial accelerometer and gyroscope - Hoo, Yong Leng (2019)
This thesis seeks to enhance expressive natural playing experience by design a virtual percussion instrument for Kompang which closely imitate the acoustic one. The thesis implemented orientation determination and expressive sound manipulation features to closely mimic the similar playing style on acoustic Kompang to provide an expressive natural playing experience to the user. A series of studies were conducted to evaluate musicians’ experience on the developed prototype. A set of initial design criteria which guided development of the prototype were then identified. An external approach was made by inviting expert musicians to use the virtual instrument, discussed their experiences and refined the criteria. A usability study was then conducted to evaluate whether the virtual instrument did enhance musicians’ playing experience in terms of expressivity and naturality. Data analysis of these studies were made via several source of data such as video recordings, log files, questionnaires. The results of the studies identified that adding orientation determination and expressive sound manipulation features can significantly improve the user experience on the virtual instrument. The orientation determination feature reminded the similar hand posture used for playing the acoustic Kompang whereas the expressive sound manipulation feature allowed musicians to dynamically manipulate the sound output based on the strength of their hand movement. Questionnaire findings indicated these features further increases simplicity, enjoyment, reality, and some other metrics, when compare to the condition in which both features were not implemented.